2016
DOI: 10.1186/s40064-016-3528-z
|View full text |Cite
|
Sign up to set email alerts
|

Embryogenesis in Polianthes tuberosa L var. Simple: from megasporogenesis to early embryo development

Abstract: The genus Polianthes belongs to the subfamily Agavoideae of the Asparagaceae family formerly known as Agavaceae. The genus is endemic to México and comprises about 15 species, among them is Polianthes tuberosa L. The aim of this work was to study and characterize the embryo sac and early embryo development of this species in order to generate basic knowledge for its use in taxonomy, in vitro fertilization and production of haploid plants and to complement studies already performed in other genera and species b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…This results in the formation of a triad composed of two chalazally placed megaspores and one binucleate cell. The triad formation has already been observed in other angiosperms (Bouman 1984; Johri et al 1992); for example, in Trifolium alexandrinum (Krupko 1973), Cytisus striatus and C. multiflorus (Rodríguez-Riaño et al 2006), Polianthes tuberosa (González-Gutiérrez and Rodríguez-Garay 2016) and also in Crassulaceae. In Crassulaceae, as in other angiosperms, the nucleus of a micropylar dyad cell can undergo meiosis II, as is in Aeonium arboreum and Rosularia sempervivum (Mauritzon 1933).…”
Section: Discussionmentioning
confidence: 70%
“…This results in the formation of a triad composed of two chalazally placed megaspores and one binucleate cell. The triad formation has already been observed in other angiosperms (Bouman 1984; Johri et al 1992); for example, in Trifolium alexandrinum (Krupko 1973), Cytisus striatus and C. multiflorus (Rodríguez-Riaño et al 2006), Polianthes tuberosa (González-Gutiérrez and Rodríguez-Garay 2016) and also in Crassulaceae. In Crassulaceae, as in other angiosperms, the nucleus of a micropylar dyad cell can undergo meiosis II, as is in Aeonium arboreum and Rosularia sempervivum (Mauritzon 1933).…”
Section: Discussionmentioning
confidence: 70%
“…Transvacuolar strands also aid in the mobility of polar nuclei, which fuse to form the central cell nucleus. In Polianthes tuberosa , another member of the Asparagaceae family, before the migration of the micropylar polar nucleus toward the chalazal end, where the other polar nucleus is located, a thin cytoplasmic strand appears traversing the central vacuole and connecting both polar nuclei ( Gonzalez-Gutierrez and Rodriguez-Garay, 2016 ). Similarly, analysis of the developmental dynamics of A. thaliana female gametophyte demonstrated that the migration of polar nuclei occurs through the middle ( Susaki et al, 2021 ) but not along the periphery of the cell ( Higaki et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%